2004
DOI: 10.1079/phn2003584
|View full text |Cite
|
Sign up to set email alerts
|

A life course approach to diet, nutrition and the prevention of chronic diseases

Abstract: Objective: To briefly review the current understanding of the aetiology and prevention of chronic diseases using a life course approach, demonstrating the lifelong influences on the development of disease. Design: A computer search of the relevant literature was done using Medline-'life cycle' and 'nutrition' and reviewing the articles for relevance in addressing the above objective. Articles from references dated before 1990 were followed up separately. A subsequent search using Clio updated the search and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
241
1
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(261 citation statements)
references
References 203 publications
(239 reference statements)
1
241
1
18
Order By: Relevance
“…A few long-term studies have shown the relationships between high blood pressure in adolescence or young adulthood and later risk of stroke or CDH in midlife [4]. This trend seems to be visible, particularly in developing countries [18].…”
Section: Life Course Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…A few long-term studies have shown the relationships between high blood pressure in adolescence or young adulthood and later risk of stroke or CDH in midlife [4]. This trend seems to be visible, particularly in developing countries [18].…”
Section: Life Course Epidemiologymentioning
confidence: 99%
“…The aim is to explore how biological, psychological, and social risk factor trajectories, acting across the whole life course, influence age-related diseases, functional decline, and disability. There is growing evidence from life course studies that adult function and age-related chronic diseases have their origins in early life experiences and share common risk actors [1,4]. The interest in this approach is not, however, new.…”
Section: What Is a Life Course Approach?mentioning
confidence: 99%
See 2 more Smart Citations
“…A lifespan perspective and emphasis on cumulative burden increasingly inform views of stress and health among adults (Darnton-Hill, Nishida, & James, 2004). McEwen (2000a) has advanced the concept of allostatic load to maintain a necessary distinction between stressors and stress: the former is a property of circumstances to which individuals are exposed, the latter is the extent to which the individual is challenged to maintain function.…”
Section: Allostatic Load and Cumulative Burdenmentioning
confidence: 99%